Depression and anxiety in people with inflammatory bowel disease. - Kurina, L; Goldacre, M; Yeates, D; Gill, L (2001)
STUDY OBJECTIVE: To determine whether depression or anxiety co-occurs with ulcerative colitis (UC) or Crohn's disease (CD) more often than expected by chance, and, if so, whether the mental disorders generally precede or follow the inflammatory bowel diseases (IBD). DESIGN: Nested case-control studies using a database of linked hospital record abstracts. SETTING: Southern England. MAIN RESULTS: Both depression and anxiety preceded UC significantly more often than would be predicted from the control population's experience. The associations were strongest when the mental conditions were diagnosed shortly before UC, although the association between depression and UC was also significant when depression preceded UC by five or more years. Neither depression nor anxiety occurred before CD more often than expected by chance. However, depression and anxiety were significantly more common after CD; the associations were strongest in the year after the initial record of CD. UC was followed by anxiety, but not by depression, more often than expected by chance and, again, the association was strongest within one year of diagnosis with UC. CONCLUSIONS: The concentration of risk of depression or anxiety one year or less before diagnosis with UC suggests that the two psychiatric disorders might be a consequence of early symptoms of the as yet undiagnosed gastrointestinal condition. The data are also, however, compatible with the hypothesis that the psychiatric disorders could be aetiological factors in some patients with UC. Most of the excess anxiety or depression diagnosed subsequent to diagnosis of IBD occurs during the year after IBD is diagnosed and the probable explanation is that the mental disorders are sequelae of IBD.